METTL3-driven m6A modification orchestrates mitophagy-dependent ferroptosis in PM2.5-induced lung injury - Ran, Qin; Gao, Jie; Li, Guoping; Wang, Junyi; Li, Xiaolan; Xiong, Anying; Zhang, Yi; Xiong, Ying; He, Xiang (Frontiers in Immunology, 2025)
Air pollution, particularly from fine particulate matter (PM2.5), poses a significant threat to respiratory health, yet the molecular mechanisms underlying PM2.5-induced lung injury remain incompletely understood. This study investigated the role of N6-methyladenosine (m6A) methyltransferase METTL3 in regulating mitophagy-dependent ferroptosis in bronchial epithelial cells exposed to PM2.5. Using in vitro and in vivo models, we demonstrated that PM2.5 exposure induced histological alterations in mouse lung tissues, including inflammatory cell infiltration, goblet cell hyperplasia, and mucus hypersecretion, concurrent with enhanced ferroptosis and mitophagy in bronchial epithelial cells. Gain-of-function and loss-of-function experiments showed that METTL3 overexpression exacerbated mitophagy and ferroptosis, while METTL3 silencing attenuated these processes, rescuing cell viability and reducing pulmonary inflammation. In vivo, intratracheal administration of METTL3 recombinant protein recapitulated these effects, confirming its role in amplifying PM2.5-induced lung injury. Mechanistically, PM2.5 upregulated METTL3 expression, which promoted PINK1 mRNA stability through m6A modification, activating the PINK1-dependent mitophagy pathway. This led to the excessive clearance of damaged mitochondria, culminating in iron-dependent lipid peroxidation, dysregulation of ferroptosis-related proteins (ACSL4 and xCT), and ferroptotic cell death. Critically, the inhibition of mitophagy with Mdivi-1 protected against histological damage and ferroptosis in mice, underscoring the therapeutic potential of targeting this pathway. Collectively, our findings established a hierarchical regulatory axis where m6A–mitophagy–ferroptosis drove lung injury. This study uncovered a novel link between epigenetic modification, mitophagy, and ferroptosis, identifying METTL3-mediated m6A modification and mitophagy as potential targets for preventing PM2.5-related respiratory diseases.